De-Coca-colonization : making the globe from the inside out - Flusty, Steven, 1963- (Routledge, 2004)
A novel theoretical account of globalization, this book argues that we must move away from top-down visions of the processes and concentrate on how ordinary people locked out of power structures create "globalities" of their own